Improvement of road safety using passive and active intelligent vehicle safety systems - Jarašūnienė, Aldona; Jakubauskas, Gražvydas (Transport, 2007)
Following the measures foreseen in the Transport White Paper 2001, situation of road safety has improved. Road fatalities have declined by more than 17 % since 2001 in the EU. However, with around 41 600 deaths and more than 1.7 million injured in 2005, road remains the least safe mode of transport and objectives to halve the number of fatalities on road by 2010 is most likely not feasible to achieve. Therefore a need for the intelligent vehicle safety systems, that enable to raise the level of road safety, is much higher than ever before. The Intelligent Vehicle Safety Systems ensure a superior safety on road would it be vehicle‐based or infrastructure‐related systems. These can be divided into passive and active safety applications where the former help people stay alive and uninjured in a crash, while the latter help drivers to avoid accidents. Some of the most promising (e‐call) and the most used (ABS, ESP) systems are analised more specifically in the paper. Possible solutions to deploying intelligent transport systems in Lithuania are also introduced. First Published Online: 27 Oct 2010